Identification of key genes for hypertrophic cardiomyopathy using integrated network analysis of differential lncRNA and gene expression - Cao, Jing; Yuan, Lei (Frontiers in Cardiovascular Medicine, 2022)
Objective: Hypertrophic cardiomyopathy (HCM) is a complex heterogeneous heart disease. Recent reports found that long non-coding RNAs (lncRNAs) play an important role in the progression of cardiovascular diseases. The present study aimed to identify the novel lncRNAs and mRNAs and find out the key pathways involved in HCM. Methods: The lncRNA and mRNA sequencing datasets of GSE68316 and GSE130036 were downloaded from the Gene Expression Omnibus (GEO) database. An integrated co-expression network analysis was conducted to identify differentially expressed lncRNAs and differentially expressed mRNAs in HCM patients. Then, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were explored to perform the biological functions and signaling pathways of co-expression network. protein‑protein interaction (PPI) and hub gene networks were constructed by Cytoscape software.HCM patients' plasma samples and GSE89714 dataset were used to validate the bioinformatic results. Results: A total of 1426 differential expressed (DE) lncRNAs and 1715 DE-mRNAs were obtained from GSE68316, of which 965 lncRNAs and 896 mRNAs were upregulated, 461 lncRNAs and 819 mRNAs were downregulated. A total of 469 DE-lncRNAs and 2407 DE-mRNAs were screened from GSE130036, of which 183 lncRNAs and 1283 mRNAs were upregulated, 286 lncRNAs and 1124 mRNAs were downregulated. A co‑expression network was constructed and contained 30 DE-lncRNAs and 63 DE-mRNAs, which were primarily involved in ‘G-protein beta/gamma-subunit complex bindingʼ, ʻpolyubiquitin modification-dependent protein bindingʼ, ‘Apelin signaling pathway’and ʻWnt signaling pathwayʼ. The expression of LA16c-312E8.2 and RP5-1160K1.3 in plasma of HCM patients were elevated and the expression of MIR22HG was decreased which were consistent with our analysis. Veriﬁcation analyses performed on GSE89714 showed 5 upregulated mRNAs of and 1 downregulated mRNAs co-expressed with 5 crucial lncRNAs. Moreover, 4 mRNAs were upregulated and 1 mRNAs were downregulated in the top 10 hub genes of PPI networks. Conclusion: These findings provide a new thought in understanding the mechanism and discovering new therapeutic targets of HCM. Three differentially expressed pivotal lncRNAs in co-expression network may serve as biomarkers and intervention targets for diagnosis and treatment of HCM. Keywords: Hypertrophic cardiomyopathy, differentially expressed long noncoding RNAs, differentially expressed mRNAs, co‑expression network, bioinformatics analysis.